CEFIXIME IN MANAGEMENT OF ENT INFECTIONS IN CHILDREN - O.A. Egorova; S.N. Kozlov (Вопросы современной педиатрии, 2008)
The data of a prevalence and etiology of main ENT infectious in children was presented in this work. The methods of choice of antibacterial medications in management of acute and chronic otitis media, acute and chronic sinusitis, acute and recurrent tonsillopharyngitis, epiglottitis were reviewed. Special accent was given to the opportunity of management of these diseases with cephalosporins and, particularly cefixime (suprax). Cefixime is peroral cephalosporin of iii generation; it combines wide range of antibacterial activity, good pharmacokinetic characteristics, favorable tolerance and comfortable application (it should be prescribed once daily). The data, obtained from many controlled trials, shows high clinical and microbiological activity of cefixime in management of ENT infections in children.Key words: children, ENT infections, cefixime, treatment.